Effect of Virtual Laboratory Experiments on Secondary School Students’ Retention in Chemistry in Jalingo Educational Zone, Taraba State - JACK, Gladys Uzezi; SHIDAWA, Emobwejwa Bwefwa (Ilorin Journal of Education, 2025)
Inadequacies accompanying the physical laboratory have made it necessary to find a complementary alternative. In line with this, the study explored the effect of virtual laboratory experiments on students’ retention in chemistry. A quasi-experimental research design was adopted for the study. The population comprised 5361 secondary school two students in Jalingo Education Zone, Taraba State, Nigeria. Multistage sampling was used to select 106 students from two intact classes: one of which was assigned to the experimental group, while the other was the control group. Students were pre-tested, and four weeks of treatment followed; thereafter, the Acid-Base Titration Achievement Test (ABTAT) was used for data collection. Two weeks later, ABTAT was reshuffled and renamed Acid-Base Retention Test (ABRT). Three experts validated the instrument, and a reliability index of 0.94 was obtained using KR-20. Mean and standard deviation were used to answer the research questions, while Analysis of Covariance (ANCOVA) was used to test the null hypotheses at 0.05 level of significance. Virtual laboratory students retained significantly higher than physical laboratory students (p<0.05). No significant difference was found in the retention of male and female students in the virtual laboratory group and there was no significant interaction effect of the practical methods and gender on students’ retention in chemistry (p>0.05). The study concluded that virtual laboratory is effective in improving students’ retention in chemistry, and recommended that chemistry teachers in conjunction with school administrators, should make provision for virtual laboratory experiments for students.